Rab25 and CLIC3 collaborate to promote integrin recycling from late endosomes/lysosomes and drive cancer progression - Dozynkiewicz, Marta A; Jamieson, Nigel B; Macpherson, Iain; Grindlay, Joan; van den Berghe, Peter V E; von Thun, Anne; Morton, Jennifer P; Gourley, Charlie; Timpson, Paul; Nixon, Colin; McKay, Colin J; Carter, Ross; et al. (Developmental cell, 2012)
Here we show that Rab25 permits the sorting of ligand-occupied, active-conformation α5β1 integrin to late endosomes/lysosomes. Photoactivation and biochemical approaches show that lysosomally targeted integrins are not degraded but are retrogradely transported and recycled to the plasma membrane at the back of invading cells. This requires CLIC3, a protein upregulated in Rab25-expressing cells and tumors, which colocalizes with active α5β1 in late endosomes/lysosomes. CLIC3 is necessary for release of the cell rear during migration on 3D matrices and is required for invasion and maintenance of active Src signaling in organotypic microenvironments. CLIC3 expression predicts lymph node metastasis and poor prognosis in operable cases of pancreatic ductal adenocarcinoma (PDAC). The identification of CLIC3 as a regulator of a recycling pathway and as an independent prognostic indicator in PDAC highlights the importance of active integrin trafficking as a potential drive to cancer progression in vivo.